TINGKAT KEPUASAN PASIEN PESERTA JKN TERHADAP MUTU PELAYANAN DI PUSKESMAS KOTA ENDE, KABUPATEN ENDE - Tokan, Rany; Regaletha, Tadeus A. L.; Sinaga, Masrida (Kelimutu Nursing Journal, 2023)
The contentment of the patient is a matter of fact after a person receives a service and provides some good assessment of the services. National Health Insurance (JKN) is a Government Program that aims to provide health insurance for all Indonesians. In 2019, the Ende city health center effectuated a survey regarding the extent of contentment of Ende city residents and the results revealed that there is a lot of lamentation that is perceived such as unsociable health workers, the retardation in handling their duties, the services that are still complicated, the unsanitary environment, the cramped waiting room, the long queue counter, and the lack of infrastructure such as the seat and parking lot. This research intends to ascertain the extent of contentment of the JKN participant's patient's contentment at the end city health center. This sort of research exerts the quantitative study specifically the descriptive survey method with a cross-sectional research design. The results of the study showed that 99.5% of JKN participant patients were satisfied with the quality of services, and only 0.5% were dissatisfied, As seen from the distribution of contentment levels, the tangible dimensions of 92% of respondents were satisfied and 8% was dissatisfied, the reliability dimensions of 95% respondents were satisfied and 5% was not satisfied, the responsiveness dimensions of 94,% respondents were satisfied while 5.8% were dissatisfied, the assurance dimension was satisfied by 95.85% respondents and 4.15% was not satisfied, the dimensions of empathy of respondents were satisfied by 95.85% respondents while 4.15 was not satisfied. Ende City Health Center is expected to be communicative and hospitable during the service process at Ende City Health Center, extend the time of attendance and it is necessary to conduct periodic and accurate surveys of contentment levels to maintain service quality by the Regulation of the Minister of Health of the Republic of Indonesia of 2016 concerning Health Service Standards which states that the fulfilment of service quality for each type of basic service in Health SPM should stand on the top of 95% or equivalent to 100%.